Intoxicación aguda por metotrexato: claves de su diagnóstico y prevención - Roberts, Michelle; Bastard, Dolores Pilar; Torre, Ana Clara; Martínez Castellanos, Carlos Ronald; Mazzuoccolo, Luis Daniel (Revista del Hospital Italiano de Buenos Aires, 2020)
-